Functional insights into the activity of Flavonoid Silymarin and the antiviral peptide L-SP40 against Enterovirus A71 - Salima, Sadruddin Lalani (2021)
Enterovirus 71 (EV-A71) is a significant etiological agent of hand foot and mouth disease (HFMD). Some strains of EV-A71 have the potential to cause severe neurological infections which could lead to death. Since there is no US-FDA approved vaccine in the global market, there is an urgent need to develop novel antivirals to prevent or treat EV-A71 infections. Two direct-acting flavonoids (baicalein and silymarin) and a host-directed L-SP40 peptide were evaluated as potential antiviral candidates. Both baicalein and silymarin were demonstrated to inhibit EV-A71 infection by direct extracellular virus blocking action with IC50 of 15.20 ± 3.53 μg/mL and 30.88 ± 5.50 μg/mL, respectively. Silymarin showed higher virus blocking with more than 80% inhibition of virus attachment. Silymarin interacted with the recombinant viral protein 1 (rVP1) of EV-A71 to exert its virus blocking effects. Molecular docking identified the binding of silymarin specifically near to the GH loop that is involved in virus-host interaction. However, the emergence of the S9 mutant with substitution from isoleucine to threonine at position 97 in the BC loop of VP1 led to the increased binding of EV-A71 to RD cells. The host-directed antiviral L-SP40 peptide, known to inhibit EV-A71 by cell protection, was further evaluated to elucidate the mechanism of action and its in vivo inhibitory potential. A pull-down assay was performed to identify the binding partner of the L-SP40 peptide and it was found to interact with nucleolin. It was further demonstrated that nucleolin co-immunoprecipitated and co-localized with the L-SP40 peptide. Knockdown of nucleolin receptor from RD cells led to a significant reduction in the viral infectivity by ~3.5 logs10 of EV-A71 strain 41 in RD cells. Similarly, a significant reduction of EV-A71 infectivity (92%) was observed by blocking nucleolin with anti-nucleolin antibody. Furthermore, L-SP40 peptide in combination with anti-receptor antibodies was observed to enhance the inhibitory effects of most of these antibodies and further reduced the residual infectivity of EV-A71 in RD cells. The L-SP40 peptide demonstrated significant (80%) protection of neonatal mice against lethal challenge by the mouse-adapted EV-A71 sub-genotype B3 (MAV). Remarkably, the L-SP40 peptide was able to substantially reduce the viral load in the blood (4.5 logs10), skeletal muscles (1.5 logs10) and brain stems (1.5 logs10) of suckling mice that were challenged and prevented severe hind limb paralysis and death. Hence, the L-SP40 peptide is proposed to serve as a potential antiviral candidate to be further evaluated for safety and potency in future clinical trials against EV-A71.